ANALYSIS OF NATURAL DAYLIGHTING AT GPIB BETHEL BANDUNG USING DIALUX EVO 10.1 SIMULATION - Puspita, Wieke Oksi; Abidin, Zidanendra Fidel; Khairunisya, Nabilla Febriani; Paramita, Beta (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2023)
Natural daylighting comes from sunlight that is reflected from outside into the building and plays an important role for the building. One of the buildings that must have good natural lighting is the Church. Natural lighting is needed to support religious activities in the Church from a functional and architectural point of view by giving a certain meaning or aesthetic value. Based on the applicable standards, the church as a place of worship has a minimum requirement of 200 lux lighting (SNI) 03-6197-2000. This study aims to determine the suitability level of natural lighting in the church with applicable standards. The method used in this study is a quantitative method with data acquisition through direct observation and simulated using DIALux Evo 10.1 software. Simulation results data in the form of lux calculations and lighting distribution. Based on the simulation results, it was found that natural lighting at GPIB Bethel Bandung did not meet the applicable standards for two effective times. Therefore, a response is needed to overcome this by increasing the number and width of window openings.